New measures of the trilemma hypothesis: Implications for Asia - Hiro Ito; Masahiro Kawai (Asian Development Bank Institute (ADBI), 2012)
We develop a new set of indexes of exchange rate stability, monetary policy independence, and financial market openness as the metrics for the trilemma hypothesis. In our exploration, we take a different and more nuanced approach than the previous indexes developed by Aizenman, Chinn, and Ito (2008). We show that the new indexes add up to the value two, supporting the trilemma hypothesis. We locate our sample economies' policy mixes in the famous trilemma triangle - a useful and intuitive way to illustrate the state and evolution of policy mixes. We also examine if the persistent deviation of the sum of the three indexes from the value two indicates an unsustainable policy mix and therefore needs to be corrected by economic disruptions such as economic and financial crises. We obtain several findings. First, such a persistent deviation can occur particularly in emerging economies that later experience an inflation (or potentially a general or a currency) crisis, and dissipates in the postcrisis period. Second, there is no evidence for this type of association between deviations from the trilemma constraint and general, banking, or debt crises. Third, Thailand experienced such a deviation from the trilemma constraint in the period leading to the baht crisis of 1997, but not other East and Southeast Asian economies. This last result suggests that the main cause for the Thai baht crisis was an unsustainable policy mix in the precrisis period, while other affected economies experienced crises mainly due to contagion from Thailand.
Keywords: F15; F 21; F31; F36; F41; O24; 330; trilemma hypothesis; trilemma triangle; exchange rate stability; monetary policy independence; financial market openness; asia; Wechselkurspolitik; Finanzmarktregulierung; Zentralbankunabhängigkeit; Policy-Mix; Wirkungsanalyse; Welt